The synaptic protein syntaxin1 is required for cellularization of Drosophila embryos. - Burgess, R.W.; Deitcher, D.L.; Schwarz, T.L. (Journal of Cell Biology, 1997)
Syntaxins are membrane proteins involved in vesicle trafficking and are required for the release of neurotransmitter at nerve terminals. The presence of syntaxins on target membranes has been hypothesized to confer specificity to targeting and fusion via interactions with complementary vesicle-associated proteins, the synaptobrevins or VAMPS. We have mutagenized syntaxin1 in Drosophila and have found that it links the mechanism of synaptic transmission to a distinct cell biological process: the cellularization of early embryos. This specialized form of cell division separates the 6,000 nuclei of the syncytial blastoderm into separate cells through the invagination of the surface membrane of the embryo. During this process, syntaxin1 protein is present on the newly forming lateral cell surfaces and invaginating cleavage furrows. This protein is derived both from maternal deposition of mRNA and protein and from early zygotic transcription. To analyze syntaxin1's role in early development, female germ line mosaics mutant for syntaxin1 expression were generated by mitotic recombination to reduce the maternal contribution. Visualizing the actin cytoskeleton and glycosylated surface proteins reveals that embryos with insufficient syntaxin1 have large acellular patches. The patches do not appear until cellularization begins, and the process fails entirely within these regions. These results provide genetic evidence that membrane trafficking is required for the cellularization of the syncytial blastoderm. We propose that the invagination of the surface membrane proceeds by the fusion of intracellular membrane vesicles with the surface. This reaction uses the same syntaxin1 protein as is required for neurotransmitter secretion at synapses. Thus, a single syntaxin can participate in trafficking steps that are functionally as distinct as synaptic transmission and cell division.